(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The aim of this research is to apply Throughput Accounting in improving the cost leadership strategy for the woven fabric department (polyester blended - polyester 150/1) in the Waist Textile and Knitting Factory. The problem of the research is that the research sample laboratory does not apply modern cost management methods represented in Throughput Accounting, as the Iraqi economic units suffer from their inability to compete in the labor market in light of the competitive environment. The Ministry of Interior improved the cost leadership strategy for the product of blended polyester and polyester fabrics 1/150. Through the research, a set of conclusions was reached, the most important of which are: Improving the cost leadership strategy through the application of achievement metrics (completion rate, achievement margin, completion time) to contribute to reducing the costs of the research sample products, A number of recommendations were also reached, the most important of which are : the need to increase the percentage of achievement margin by increasing sales by applying the cost leadership strategy (Reducing the cost of production) to reach a reduced cost compared to competing products in the market.